Design and operation of a continuous integrated monoclonal antibody production process. (21st August 2017) - Steinebach, Fabian; Ulmer, Nicole; Wolf, Moritz; Decker, Lara; Schneider, Veronika; Wälchli, Ruben; Karst, Daniel; Souquet, Jonathan; Morbidelli, Massimo
Abstract : The realization of an end‐to‐end integrated continuous lab‐scale process for monoclonal antibody manufacturing is described. For this, a continuous cultivation with filter‐based cell‐retention, a continuous two column capture process, a virus inactivation step, a semi‐continuous polishing step (twin‐column MCSGP), and a batch‐wise flow‐through polishing step were integrated and operated together. In each unit, the implementation of internal recycle loops allows to improve the performance: (a) in the bioreactor, to simultaneously increase the cell density and volumetric productivity, (b) in the capture process, to achieve improved capacity utilization at high productivity and yield, and (c) in the MCSGP process, to overcome the purity‐yield trade‐off of classical batch‐wise bind‐elute polishing steps. Furthermore, the design principles, which allow the direct connection of these steps, some at steady state and some at cyclic steady state, as well as straight‐through processing, are discussed. The setup was operated for the continuous production of a commercial monoclonal antibody, resulting in stable operation and uniform product quality over the 17 cycles of the end‐to‐end integration. The steady‐state operation was fully characterized by analyzing at the outlet of each unit at steady state the product titer as well as the process (HCP, DNA, leached Protein A) and product (aggregates, fragments) related impurities. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1303–1313, 2017